Silver Nanoparticles: Understanding the Interaction of Glutamate Salts with Serum Albumin Protected Prism‐Shaped Silver Nanoparticles toward Glutamate Sensing (Part. Part. Syst. Charact. 1/2019). (9th January 2019) - Zeng, Yuan; Chang, Yu‐Hsin; Gharib, Mustafa; Parak, Wolfgang J.; Chakraborty, Indranath
Abstract : In article number1800229, Yuan Zeng, Indranath Chakraborty, and co‐workers have used a BSA protected prism‐shaped silver nanoparticle (Ag@BSA NP)‐based surface plasmon resonance (SPR) spectroscopy tool to detect glutamate salts. The cover picture demonstrates the mechanism of this process which revealed that Ag@BSA NPs were transformed into smaller sized nanoclusters through an etching process induced by high concentrations of monosodium glutamate, similar to an "ant‐driven food breaking process", while the remaining nanoparticles are assembled to form aggregates.